Birth and Death of Human β-Cells in Pancreases from Cadaver Donors, Autopsies, Surgical Specimens, and Islets Transplanted into Mice. Issue 2 (March 2014) - Caballero, Francisco; Siniakowicz, Karolina; Hollister-Lock, Jennifer; Duran, Luisa; Katsuta, Hitoshi; Yamada, Takatsugu; Lei, Ji; Deng, Shaoping; Westermark, Gunilla T.; Markmann, James; Bonner-Weir, Susan; Weir, Gordon C.
There is great interest in the potential of the human endocrine pancreas for regeneration by β-cell replication or neogenesis. Our aim was to explore this potential in adult human pancreases and in both islet and exocrine tissue transplanted into mice. The design was to examine pancreases obtained from cadaver donors, autopsies, and fresh surgical specimens and compare these findings with those obtained from islet and duct tissue grafted into the kidney. Islets and exocrine tissue were transplanted into normoglycemic ICR-SCID mice and studied 4 and 14 weeks later. β-Cell replication, as assessed by double staining for insulin and Ki67, was 0.22±0.03% at 4 weeks and 0.13±0.03% at 14 weeks. In contrast, no evidence of β-cell replication could be found in 11 cadaver donor and 10 autopsy pancreases. However, Ki67 staining of β-cells in frozen sections obtained at surgery was comparable to that found in transplanted islets. Evidence for neogenesis in transplanted pancreatic exocrine tissue was supported by finding β-cells within the duct epithelium and the presence of cells double stained for insulin and cytokeratin 19 (CK19). However, β-cells within the ducts never constituted more than 1% of the CK19-positive cells. With confocal microscopy, 7 of 12 examined cells expressed both markers, consistent with a neogeneic process. Mice with grafts containing islet or exocrine tissue were treated with various combinations of exendin-4, gastrin, and epidermal growth factor; none increased β-cell replication or stimulated neogenesis. In summary, human β-cells replicate at a low level in islets transplanted into mice and in surgical pancreatic frozen sections, but rarely in cadaver donor or autopsy pancreases. The absence of β-cell replication in many adult cadaver or autopsy pancreases could, in part, be an artifact of the postmortem state. Thus, it appears that adult human β-cells maintain a low level of turnover through replication and neogenesis.